Long COVID: long-term effects?. (8th October 2021) - Di Toro, Alessandro; Bozzani, Antonio; Tavazzi, Guido; Urtis, Mario; Giuliani, Lorenzo; Pizzoccheri, Roberto; Aliberti, Flaminia; Fergnani, Viola; Arbustini, Eloisa
Abstract: The term Long COVID (or Post COVID) describes a condition characterized by persistence of symptoms for at least 12 weeks after the onset of COVID-19. It may last several months but the duration is still matter of observation. The symptoms and the clinical manifestations are clinically heterogeneous and suggesting involvement of multi-organs/systems, including the cardiovascular system. The general recurrent symptoms include fatigue, breathlessness, myalgia, headache, loss of memory, and impaired concentration. Patients report loss of their previous psychophysical performance. Cardiovascular involvement manifests with common symptoms such as palpitations and chest pain, and, less commonly, with events such as late arterial and venous thromboembolisms, heart failure episodes, strokes or transient ischaemic attack, 'myo-pericarditis'. The diagnostic criteria are mainly based on the narrative of the patients. Measurable biomarkers or instrumental findings or clinical events are not yet framed in a shared diagnostic framework. The open question for clinicians and researchers is whether biomarkers, electrocardiogram, non-invasive imaging, and clinical monitoring should be included in a shared diagnostic protocol aimed at defining the diagnostic path and protecting patients at risk of unexpected events.